Konsep Kurikulum Pendidikan Islam Holistik Telaah Pemikiran Ikhwan As-Shafa - Benny Kurniawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Insitut Agama Islam Nahdlatul Ulama (IAINU) Kebumen, 2020)
Looking at the Islamic world, where Islam was empowered in its role as a bridge between Greek civilization and Europe in the Middle Ages, the principles of holistic education as described above were actually initiated much earlier by Islamic thinkers, namely the Ikhwan as-Shafa in the 10th century AD. The Ikhwan as-Shafa is a secret and mysterious organization consisting of Muslim Arab philosophers based in Basrah, Iraq at that time was the capital of the Abassiyah caliphate around the 10th century AD (373H/983). The group that was born in Basra is famous for its treatises, which contain their spiritual doctrines and philosophical systems. Through Rasail Ikhwan as-Shafa's magnum opus, information can be obtained about the traces of their teachings, both regarding science, philosophy and religion.